Dielectric properties and compositional analysis of banana (Musa Sapientum Linn) and relationship to ripening - K. Sirikulrat (2018)
© 2015 American Society of Agricultural and Biological Engineers. The compositions of bananas (Musa sapientum Linn) of various ages after flowering, from young bananas to mature unripe and ripe bananas, were analyzed and their dielectric properties were investigated by using two dielectric plates in a parallel model. Mathematical analysis of the measurement system was proposed and verified for reliability and accuracy. The dielectric properties were measured using a precision impedance analyzer in the frequency range of 100 Hz to 1 MHz. Average relative permittivities of about 20 to 40 and 13 to 23 were obtained for fresh and dried bananas, respectively. The results clearly indicate that the high moisture content and the ripening stage affect the relative permittivity with a p-value from ANOVA of less than 0.0005. The increase in relative permittivity after ripening and the carbohydrate content were found to have a linear relationship with an R < sup > 2 < /sup > value of 0.958. Continuous measurement of mature unripe bananas at different ripening stages showed that the relative permittivity was rather constant with a value of about 30, and it increased rapidly after the bananas ripened fully. The high increase in the relative permittivity correlated with the increase in carbohydrate content during ripening in combination with the high moisture content of fresh ripe bananas. The results and measurement techniques developed from this study could be used as a simple nondestructive test for indication of banana ripeness and the changes in carbohydrate content during ripening, and it is expected that similar techniques could be beneficial for further applications with other kinds of crops.